Can Economic Development Programs Be Evaluated? - Timothy J. Bartik; Richard D. Bingham (W.E. Upjohn Institute for Employment Research, 1995)
The question addressed in this paper seems simple: Can economic development programs be evaluated? But the answer is not simple because of the nature of evaluation. To determine a program's effectiveness requires a sophisticated evaluation because it requires the evaluator to distinguish changes due to the program from changes due to nonprogram factors. The evaluator must focus on the outcomes caused by the program rather than the program's procedures. Evaluations can be divided into two categories process or formative evaluations and outcome, impact, or summative evaluations. Process evaluations focus on how a program is delivered. Impact evaluations focus on the program's results. Although process evaluations are important, the focus of this chapter is on program outcomes thus the concern with impact evaluations; however, both types of evaluations need to be defined.
Additional information: A revised version of this paper appears in R. Bingham and R. Mier, eds. 1997. Dilemmas of Urban Economic Development: Issues in Theory and Practice. Thousand Oaks, CA: Sage Publications, pp. 246-277.
Keywords: J0; O2; R0; 330; economic; development; programs; evaluate; Bartik; Bingham